The Effect of Chemical Fertilizers on The Magnetic Susceptibility Value and Soil Fertility of Paddy Soils in Surantih, Kabupaten Pesisir Selatan - Maidani, Delvi Putri; Rifai, Hamdi; Dwiridal, Letmi; Mufit, Fatni (Universitas Negeri Malang, 2023)
Pesisir Selatan is a district where population depends on agriculture such as lowland rice. The rice seeds used were IR66. Efforts to improve the quality of Paddy soils seeds are fertilizing with chemical fertilizers. Chemical fertilizers used are Urea, KCL and Phonska. Continuous and excessive use of fertilizers will cause a decrease in the level of soil fertility due to the reaction between fertilizer minerals and soil minerals which also affects the magnetic susceptibility value. Based on these problems, further research was carried out to see the difference in the magnetic susceptibility value of paddy soils to the use of chemical fertilizers using the rock magnetism method with magnetic susceptibility parameters. The results showed that the paddy soil before and after being planted with rice seeds using chemical fertilizers decreased and increased the value of magnetic susceptibility due to the reaction between mineral fertilizers and soil minerals and waterlogging during the cultivation process. Meanwhile, the paddy soil before and after planting rice seeds that did not use chemical fertilizers decreased the magnetic susceptibility value quite far due to the absence of other mineral additions in the paddy soil such as chemical fertilizers.